Impact of nitrogen and potassium fertigation on sour orange (Citrus aurantium) seedlings to reach optimal budding stage - Mahmoud, Husameldin; Mohammed, Mayada; Alturki, Saleh; Emam, Abda; Hadid, Maha (Edelweiss Applied Science and Technology, 2025)
The study aimed to assess effect of nitrogen and potassium fertigation on the growth of Citrus aurantium rootstock seedlings, to reduce the period required for their readiness for grafting. The results indicated that treating Citrus aurantium seedlings with nitrogen and potassium fertilizers at a concentration of 2.5 ml/L /L significantly enhanced the vegetative growth parameters, including the number of leaves, number of branches, leaf area, plant height and stem circumference, compared to other concentrations and control treatment. Additionally, the study demonstrated the positive effect of nitrogen and potassium fertigation at a 2.5 ml/L/L concentration, in reducing the time required for the seedlings to reach a suitable stem thickness for grafting with in short period, 160 days (5 months and 10 days) only. Based on the results of this study, it is recommended to use a fertigation application of nitrogen and potassium at a concentration of 2.5 ml/L for the optimal growth of Citrus aurantium rootstock seedlings. Moreover, this treatment shortens the time required for seedlings to reach an ideal stem thickness for grafting.